2016
DOI: 10.1186/s12882-016-0242-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal abnormalities among HIV infected children at Muhimbili National Hospital (MNH)—Dar es Salaam, Tanzania

Abstract: BackgroundHuman Immunodeficiency Virus infection is a multisystem disease that contributes to significant morbidity. Renal involvement is reported to be common among patients with HIV. This study was carried out to determine renal involvement using simple bedside tests combined with ultrasonography examination.MethodsWe recruited 240 children from the HIV clinic at Muhimbili National Hospital. Data were collected using structured questionnaires and included demographic, clinical information, radiological tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
23
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 26 publications
13
23
5
Order By: Relevance
“…The most recent and similar study done in Tanzania [14] found prevalence at 20.4% which is close to that demonstrated by our study (18.9%) though it assessed HIV − infected children. However, a study from South Africa [8] found the prevalence of microalbuminuria at 24.0%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The most recent and similar study done in Tanzania [14] found prevalence at 20.4% which is close to that demonstrated by our study (18.9%) though it assessed HIV − infected children. However, a study from South Africa [8] found the prevalence of microalbuminuria at 24.0%.…”
Section: Discussionsupporting
confidence: 91%
“…This study looked at HIV − infected ART naïve patients attending the Mulago ISS clinic and the prevalence of microalbuminuria reported was different from most of the studies conducted in recent times [5,6,[8][9][10][11][12][13][14]. It was challenging to compare this study with those conducted earlier due to several factors which include differing study participants and sample sizes, in addition to varying assay techniques and methodologies.…”
Section: Discussionmentioning
confidence: 88%
“…The occurrence of microalbuminuria is not related to age. This result is similar to the results reported by Fredrick [16], who observed that microalbuminuria was equally distributed across all age groups, suggesting that, regardless age, there is a continuum of renal features from the microalbuminuria which progresses towards proteinuria. On the other hand, Eke et al [14] showed that microalbuminuria is more likely to occur in older children.…”
Section: Discussionsupporting
confidence: 91%
“…and 28.8% in works by Fredick [16] and Mosten [17], both from Tanzania. Dimock [18] from Bethesda in US reported a prevalence of 15%.…”
Section: Discussionmentioning
confidence: 95%
“…This high prevalence of microalbuminuria highlights the magnitude of early renal dysfunction in HIV-infected patients before ART initiation. This was different from most of the studies conducted in recent times [5][6][7][8][9][10][11][12][13].…”
Section: Discussioncontrasting
confidence: 79%